2018 IEEE 20th International Conference on High Performance Computing and Communications; IEEE 16th International Conference On 2018
DOI: 10.1109/hpcc/smartcity/dss.2018.00116
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Optimization of Sparse Matrix-Vector Multiplication on Emerging Many-Core Architectures

Abstract: Sparse matrix vector multiplication (SpMV) is one of the most common operations in scientific and highperformance applications, and is often responsible for the application performance bottleneck. While the sparse matrix representation has a significant impact on the resulting application performance, choosing the right representation typically relies on expert knowledge and trial and error. This paper provides the first comprehensive study on the impact of sparse matrix representations on two emerging many-co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 50 publications
0
24
0
Order By: Relevance
“…Their approach of feature extraction is thus orthogonal to our machine learning based approach. Our prior work shows that selecting the right SpMV format on ARM-based many-cores is non-trivial [6]. This work builds upon our past work to show how machine learning can be employed to obtain a deep insights on how to optimize SpMV on such architectures.…”
Section: Related Workmentioning
confidence: 91%
See 1 more Smart Citation
“…Their approach of feature extraction is thus orthogonal to our machine learning based approach. Our prior work shows that selecting the right SpMV format on ARM-based many-cores is non-trivial [6]. This work builds upon our past work to show how machine learning can be employed to obtain a deep insights on how to optimize SpMV on such architectures.…”
Section: Related Workmentioning
confidence: 91%
“…Thus, the choice of K can have an impact of the SpMV performance. In this experiment, we compare two algorithms for choosing K: an average based algorithm [6] and a "histogram" based scheme [2]. This evaluation is performed on four matrices listed in Figure 5(a) to keep the experiments manageable.…”
Section: Hybmentioning
confidence: 99%
“…Shizhao Chen, perform a comprehensive study on representation of sparse matrix on Intel Knights landing XeonPhi and ARM-based FT-200PLUS architecture, they found that best representation of sparse relay on architecture and the unit of program, in their paper they use very well known CSR,CSR5,ELL,SELL and HYB sparse matrix storage format [27].…”
Section: F Compressed Sparse Row-vi(csr-vi)mentioning
confidence: 99%
“…Our adaptive model selection approach allows one to select which model to use based on the input, and is also useful when cloud offloading is prohibitively because of the latency requirement or the lack of connectivity. Machine learning has been employed for various optimization tasks [47,57], including code optimization [6,9,17,37,38,52,[54][55][56][58][59][60][61], task scheduling [10,12,15,16,44], etc. Our approach is closely related to ensemble learning where multiple models are used to solve an optimization problem.…”
Section: Related Workmentioning
confidence: 99%